How do consumers value airline services attributes? A stated preferences discrete choice model approach - Pereira, Pedro Telhado (2021)
We implement a stated preferences choice game and estimate a conditional logit model to learn the determinants of airline choice and to quantify consumers' willingness to pay for airline services attributes such as flight frequency, punctuality warranties and comfort in the Portuguese air corridor between Madeira and Oporto; the third and second most important Portuguese airports, respectively. We show that our stated preferences discrete choice model exercise is a cost effective way for airline marketing managers to elicit consumer preferences and willingness to pay measures which are quite valuable to make airline operations more effective.